A Study on Malicious Software Affecting Computer Network Security and Prevailing Techniques in the Big Data Era - Induja, S. (Indian Journal of Computer Science, 2025)
With the coming of the World Wide Web and the rise of e-commerce sites and social media platforms, businesses around the world are creating a huge amount of data every day. Information security is one of the most important things to make sure data is sent safely over the internet. Also, network security is becoming more important as society moves towards a digital age. As more people use the internet, it also brings more chances for cyber attacks. It is necessary to protect computers and networks which are key concerns. Harmful systems can cause problems in the network. They can use resources from different systems to protect their own. The present paper gives an overview of network security and the different methods that can help improve it, such as Cryptography.